1988
DOI: 10.1021/bi00412a022
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of the interaction of the antibiotic nogalamycin with the hexadeoxyribonucleotide duplex d(5'-GCATGC)2

Abstract: 1H resonance assignments in the NMR spectra of the self-complementary hexadeoxyribonucleoside pentaphosphate d(5'-GCATGC)2 and its complex with the antibiotic nogalamycin, together with interproton distance constraints obtained from two-dimensional nuclear Overhauser effect (NOE) spectra, have enabled us to characterize the three-dimensional structure of these species in solution. In the complex described, two drug molecules are bound per duplex, in each of two equivalent binding sites, with full retention of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
66
2
3

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 37 publications
12
66
2
3
Order By: Relevance
“…The interaction of the anthracyclin¢ antibiotic, nogalamycin, with the hexamer duplex d(GCATGC)~ has previously been shown to induce significant perturbations of base and sugar proton chemical shifts [3], alter the position of the conformational equilibrium of the deoxyribose rings [14] and cause large down-field shifts of two of the five phosphate resonances [3]. The data are consistent with a significant drug-induced alteration of the average solution conformation of the hexamer duplex.…”
Section: Discussionsupporting
confidence: 56%
“…The interaction of the anthracyclin¢ antibiotic, nogalamycin, with the hexamer duplex d(GCATGC)~ has previously been shown to induce significant perturbations of base and sugar proton chemical shifts [3], alter the position of the conformational equilibrium of the deoxyribose rings [14] and cause large down-field shifts of two of the five phosphate resonances [3]. The data are consistent with a significant drug-induced alteration of the average solution conformation of the hexamer duplex.…”
Section: Discussionsupporting
confidence: 56%
“…It does not follow that drugs will consistently adopt a common mode of interaction at all possible sites, as Fox and Waring (1986) were forced to conclude in respect of the orientation of nogalamycin bound to DNA and others have since clarified (Searle et al, 1988;Egli et al, 1991 ;van Houte et al, Definitive evidence for bis-intercalation via the major groove of the helix will have to await the determination of a high-resolution structure for an oligonucleotidehis-naphthalimide complex by NMR or X-ray crystallography, as has been achieved for ditercalinium (Williams and Gao, 1992). Efforts to obtain structural data by these means are under way.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative arrangement with the drug rotated by 1800 relative to the DNA was also proposed (17). However, with 1H NMR spectroscopy Wakelin and coworkers (14) have shown that nogalamycin intercalates at the TpG step of [d(GCATGC)]2 in the orientation proposed by Arora, with the nogalose in the minor groove and the fused bicyclo amino sugar in the major groove.…”
mentioning
confidence: 95%
“…Nogalamycin has been shown by a variety of techniques to penetrate the DNA helix and form a stable, intercalative complex (8)(9)(10)(11)(12)(13)(14) with slow association and dissociation rates (17). The crystal structure and relative stereochemistry of nogalamycin were determined by Arora (18), who proposed a model DNA-nogalamycin-complex.…”
mentioning
confidence: 99%